Richard Kearney and Kascha Semonovitch (eds.), Phenomenologies of the Stranger - Kris Sealey (Journal of French and Francophone Philosophy, 2012)
Review of Richard Kearney and Kascha Semonovitch (eds.), Phenomenologies of the Stranger: Between Hostility and Hospitality